Taenia solium Cysticercosis and Taeniosis Reporting in the Current Medical and Veterinary Diseases Reporting Systems in Tanzania: A Cross-Sectional Study - Fredy Mlowe; James Mlangwa; Ernatus Mkupasi; Andrea S. Winkler; Antony D. Nyerere; Ayubu Churi; Helena Ngowi; Esron Karimuribo (Veterinary Medicine International)
Taenia solium cysticercosis and taeniosis (TSCT) are two forms of a zoonotic disease caused by T. solium tapeworm. Towards promotion of a One Health approach to the control of TSCT, we assessed TSCT reporting in the medical and veterinay sectors in Tanzania. We conducted a cross-sectional study between January and April 2020 in Babati and Mbulu districts (northern Tanzania), Kongwa district (central Tanzania), Mbinga and Nyasa districts (southern Tanzania), and the Zonal Veterinary Centres in Iringa (southern Tanzania) and Arusha (northern Tanzania) regions. A questionnaire was administered to 154 officers in charge (OsIC) of primary healthcare facilities (PHFs) and 110 meat inspectors (MIs) to collect quantitative data. Key informant interviews (KIIs) were conducted to 16 medical and 17 veterinary officers from level one healthcare facilities and district livestock offices, respectively, to their respective ministries. OsIC admitted absence of specific reporting (100%, n = 154) of T. solium taeniosis and neurocysticercosis (NCC) in the medical diseases reporting system (MDRS) despite the presence of optimum facilitation in terms of report preparation and submission (92.2%, n = 154) with 83.8% (n = 154) timely report submission rate. The veterinary diseases reporting system (VDRS) accommodated porcine cysticercosis (PCC) reporting. Nevertheless, approximately 77.3% (n = 110) of the MIs admitted inadequate facilitation in VDRS that hindered efficient reporting of PCC among other diseases. In addition, all MIs admitted that disease reports submitted were incomplete, submitted late (73.3%, n = 110), or not submitted at all (88.8%, n = 110). Similarly, KIIs results revealed suboptimal facilitation and reporting efficiency in VDRS than it was with the MDRS. It is concluded that the MDRS did not provide for specific reporting of taeniosis and NCC. Inadequate facilitation of the general VDRS hindered efficient PCC reporting despite its provision for PCC reporting. A One Health approach in strengthening the medical and veterinary diseases reporting systems for efficient TSCT reporting is recommended.